Efficient α-Mannosylation of Phenols: The Role of Carbamates as Scavengers for Activated Glycosyl Donors - Schüler, Peter; Fischer, Sebastian N.; Marsch, Michael; Oberthür, Markus (Synthesis, 2013)
The boron trifluoride activation of trichloroacetimidate donors was found to be an efficient method for the α-mannosylation of tyrosine-containing acceptors. Most notably, these conditions are compatible with the commonly used carbamate protecting groups, whereas trichloroacetimidate activation with trimethylsilyl triflate or the use of glycosyl sulfoxides led to diminished yields in the presence of carbamates. In these cases, the competing reaction of the activated donors with the carbamate group was identified as a problematic side reaction. Taking advantage of this reactivity, various glycosyl carbamates were generated for the first time under non-acidic glycosylation conditions by reaction of different Boc-protected amino acids and dipeptides with glycosyl sulfoxides under triflic anhydride activation.
Keywords: glycosylation; natural products; phenols; sulfoxides; trichloroacetimidates